Global health post-2015: the case for universal health equity - Lucia D'Ambruoso (Taylor & Francis Group, 2013)
Set in 2000, with a completion date of 2015, the deadline for the Millennium Development Goals is approaching, at which time a new global development infrastructure will become operational. Unsurprisingly, the discussions on goals, topics, priorities and monitoring and evaluation are gaining momentum. But this is a critical juncture. Over a decade of development programming offers a unique opportunity to reflect on its structure, function and purpose in a contemporary global context. This article examines the topic from an analytical health perspective and identifies universal health equity as an operational and analytical priority to encourage attention to the root causes of unnecessary and unfair illness and disease from the perspectives of those for whom the issues have most direct relevance.